Differences between motivations and leisure and free time activities in sporty and non-sporty teenagers - V. Carratalá; A. García (Asociación Española de Ciencias del Deporte, 2010)
The present study describes the Scales of Sport Motivations and Activities of Leisure and Free Time and it analyzes the differences in the motivations and leisure activities and free time between adolescent sportsmen and non sportsmen. The sample of the investigation is composed by 464 non sportsmen, of which 200 are men and 263 women, and 589 sportsmen federated in the sports of Judo and Basketball, of which 394 are men and 195 women, all them of ages understood between the 15 and 17 years. KEY WORDS: Motivation, Leisure, Free Time, Adolescents.